Chemical Diversification of Sialic Acid Glycosides by Stereospecific, Chemoselective Deamination - Navuluri, Chandrasekhar (2013)
[Image: see text] Nitrosation of peracetylated NeuAc glycosides followed by treatment with sodium trifluoroethoxide and then a suitable nucleophile enables late stage modification of sialic acid glycosides with stereospecific replacement of the acetamido functionality.